Appendiceal mucinous cystadenocarcinoma with mural nodules of anaplastic carcinoma and K-RAS mutation - Kır, Gözde; Coşan Sarbay, Billur; Girgin, Burçin; Özen, Filiz (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Kır G, Coşan Sarbay B, Girgin B, Özen F. Appendiceal mucinous cystadenocarcinoma with mural nodules of anaplastic carcinoma and K-RAS mutation. Turk J Gastroenterol 2018; 29: 708-10.